2019
DOI: 10.1002/jcp.28920
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐329 upregulation impairs the HMGB2/β‐catenin pathway and regulates cell biological behaviors in melanoma

Abstract: Melanoma is responsible for the majority of deaths caused by skin cancer. Antitumor activity of microRNA-329 (miR-329) has been seen in several human cancers. In this study, we identify whether miR-329 serves as a candidate regulator in melanoma. Melanomarelated differentially expressed genes were screened with its potential molecular mechanism predicted. Melanoma tissues and pigmented nevus tissues were collected, where the levels of miR-329 and high-mobility group box 2 (HMGB2) were determined. To characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
(69 reference statements)
1
19
1
Order By: Relevance
“…cdh1 (E-cadherin) is a core component of adherens junctions along with a-catenin and 1-catenin 23 . Interestingly, HMGB2 and 1-catenin have been reported to cooperate to promote melanoma progression 24 . These data demonstrate one of likely many signaling interactions that occur between interface cells and other cells adjacent to the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…cdh1 (E-cadherin) is a core component of adherens junctions along with a-catenin and 1-catenin 23 . Interestingly, HMGB2 and 1-catenin have been reported to cooperate to promote melanoma progression 24 . These data demonstrate one of likely many signaling interactions that occur between interface cells and other cells adjacent to the tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang, Lu, and Gao (2019) identified that HMGB2 promoted proliferation of cervical cancer cells by activating AKT pathway. HMGB2 has also been proved to be involved in the regulation of the melanoma cell proliferation by inactivating the β‐catenin signaling pathway (Mo et al, 2019). Hence it is speculated that HMGB2 regulates cell proliferation through diverse mechanisms in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that knockdown of ADAM10 could inhibit the E-cadherin/β-catenin signaling pathway. Furthermore, β-catenin could regulate its target genes including MMP-9, Cyclin D1, c-Myc, and Survivin [33][34][35][36]. Knockdown of ADAM10 decreased the levels of those target genes, also indicating that ADAM10 could regulate E-cadherin/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 97%